Career paths and career choice factors of medical school graduates working in the Daejeon, Sejong, and Chungcheongnam-do region: a retrospective observational study - So-Young Lee; Jeong Lan Kim (Korean Journal of Medical Education)
Purpose This study analyzed the career paths of medical school graduates in the Daejeon, Sejong, and Chungcheongnam-do (DSC) region of South Korea, focusing on career choice factors at each career path. The ultimate goal was to derive practical insights to improve career guidance in the medical field and enhance professionalism. Methods Data were collected through in-depth interviews with 10 medical school graduates working in the DSC region. A semi-structured questionnaire was used to explore their career paths, and factors influencing their career decisions. The collected qualitative data were analyzed using the constant comparative method to identify themes and categories. Results The study results categorized career stages into three phases: “entering medical school,” “choosing a specialty after graduation,” and “choosing a workplace after training.” Career choice factors were classified into “personal factors,” “social factors,” and “job and work environment factors.” The factors influencing career choices differed across each career path. Conclusion This study holds significance in its in-depth analysis of career choice factors across different career paths from a long-term perspective. The findings suggest that effective support for career decision-making in the medical field requires a tailored approach that considers the distinct needs and influencing factors at each career path.